Factors Associated with Post-Sternotomy Wound Infection: A Meta-Analysis - Aris Widiyanto; Sri Iswahyuni; Krisnanda Aditya Pradana; Perdana Prabasari Putri Ichsani; Rina Tri Handayani; Hakim Anasulfalah; Ahmad Syauqi Mubarok; Joko Tri Atmojo (Masters Program in Public Health, 2026)
Background: Sternal wound infection is a serious complication following cardiac surgery, contributing to increased morbidity, mortality, and length of hospital stay. Obesity, diabetes mellitus, smoking habits, and re-operation are suspected to contribute to the incidence of post-sternotomy wound infections. This study aimed to estimate the magnitude of the influence of obesity, diabetes, smoking, and re-operation as risk factors for post-sternotomy wound infections. Subject and Method: This study is a systematic review and meta-analysis. Articles were obtained from databases including PubMed, Google Scholar and ScienceDirect, limited to publications from 2015 to 2025. The keywords and MeSH terms used were: “sternotomy, AND sternal wound infection OR deep sternal wound infection OR surgical site infection, AND “obesity OR body mass index, AND diabetes mellitus OR hyperglycemia AND smoking OR tobacco use AND re-operation AND cardiac surgery”. Article selection was based on eligibility criteria defined using the PICO model: P = patients post-sternotomy; I = obesity, diabetes, smoking, re-operation; C = non-obese, non-diabetic, non-smokers, no re-operation; O = post-sternotomy wound infection. Only full-text articles with a cross-sectional study design were included. Data were analyzed using RevMan version 5.3. Results: A total of 16 articles were included in this meta-analysis, originating from Finland, Denmark, Australia, Saudi Arabia, Colombia, Italy, France, China, Pakistan, Brazil, and United States. The meta-analysis showed that the risk of post-sternotomy wound infection was significantly increased in patients with obesity (aOR = 1.50; 95% CI: 1.31–1.72; p < 0.001), diabetes (aOR = 2.02; 95% CI: 1.26–3.25; p = 0.004), smoking (aOR = 2.44; 95% CI: 1.36–2.27; p = 0.05), obstructive sleep apnea (aOR = 1.76; 95% CI: 1.36–2.27; p < 0.001), and re-operation (aOR = 2.90; 95% CI: 1.49–5.64; p = 0.002). All findings were statistically significant. Conclusion: Risk of sternal wound infection post-sternotomy significantly increases with obesity, diabetes, smoking, and re-operation.